Seasonal changes in physical qualities of elite youth soccer players according to maturity status: Comparisons with aged matched controls - Morris, R.; Emmonds, S.; Jones, B.; Myers, T. D.; Clarke, N. D.; Lake, J.; Ellis, M.; Singleton, D.; Roe, G.; Till, K. (Science and Medicine in Football, 2018)
Purpose: Longitudinal studies assessing the seasonal development of strength, speed and power qualities are limited in youth soccer players. The purpose of this study was to evaluate the seasonal changes in the physical development of elite youth soccer players across Pre-, Circa- and Post-Peak Height Velocity (PHV), against a similar age and maturity matched control groups. Methods: One-hundred and twelve male elite youth soccer players (Pre-PHV n = 55; Circa-PHV n = 21; Post-PHV n = 36) and 38 controls consisting of non-elite active participants (Pre-PHV n = 18; Circa-PHV n = 10; Post-PHV n = 10) all undertook isometric mid-thigh pull strength, 10-30 m sprints, change of direction speed (CODs) and countermovement jump (CMJ) tests pre- and post-season. Results: The elite Circa-PHV improved greater than the control group for all physical qualities between pre- and post-season. The elite Pre-PHV improved greater in sprints, CODs, CMJ jump height and strength while the elite Post-PHV group improved more in CODs and strength than their respective control groups. Conclusion: Findings suggest that systematic academy soccer training enhances the development of physical qualities in youth soccer players but maturity status may impact upon such adaptations.